History by numbers : an introduction to quantitative approaches - Hudson, Pat, 1948-; Ishizu, Mina. (London ; New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"Fully updated and carefully revised, this new 2nd edition of History by Numbers still stands alone as the only textbook on quantitative methods suitable for students of history. Even the numerically challenged will find inspiration. Taking a problem-solving approach and using authentic historical data, it describes each method in turn, including its origin, purpose, usefulness and associated pitfalls. The problems are developed gradually and with narrative skill, allowing readers to experience the moment of discovery for each of the interpretative outcomes. Quantitative methods are essential for the modern historian, and this lively and accessible text will prove an invaluable guide for anyone entering the discipline"--
1. The Prospects and Pitfalls of History by Numbers -- 2. The Origins and Nature of Quantitative Thinking -- 3. Arranging, Rearranging and Displaying Data -- 4. Summarising Data : Averages and Distributions -- 5. Time Series and Indices -- 6. Relationships Between Variables -- 7. Sampling and Significance Testing -- 8. Economic History and Econometric History -- 9. Historical Research, Computing and the Digital Revolution -- Glossary.
Includes bibliographical references (pages 307-330) and index.
Keywords: History -- Statistical methods; History -- Research -- Statistical methods; HISTORY / General